Atherosclerosis of the carotid arteries: clinical significance (a literature review) - M. A. Fedorina; I. L. Davydkin; O. A. Germanova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
Сarotid atherosclerotic disease increase the risk of ischemic stroke, with various clinical manifestations from asymptomatic to fatal. Cerebral blood flow depends not only on the degree of stenosis, but also on the patency of the collateral tract, affecting the severity of the clinical picture. Criteria for the hemodynamic significance of carotid artery stenosis and, based on them, indications for surgical treatment have been developed. But there is a group of patients with asymptomatic carotid stenosis and borderline values in assessing the hemodynamic significance of atherosclerotic plaques, who remain at risk of ischemic stroke. Thus, there is a need to assess the collateral cerebral circulation, and the impact of the degree of stenosis on cerebral perfusion. Also of interest is the assessment of hemodynamics at the site of carotid stenosis and the assessment of cerebral autoregulation during exercise testing. This will help in selecting patients with asymptomatic carotid stenosis who are at increased risk of stroke and who would benefit from revascularization.